Cultural Similarities in Perfectionism: Perfectionistic Strivings and Concerns Generalize Across Chinese and Canadian Groups. (January 2016) - Smith, Martin M.; Saklofske, Donald H.; Yan, Gonggu; Sherry, Simon B.
This study supports the generalizability of perfectionistic strivings and concerns across Canadian and Chinese university students ( N = 1, 006) and demonstrates the importance of establishing measurement invariance prior to hypothesis testing with different groups. No latent mean difference in perfectionistic concerns was observed, but Canadian individuals reported higher perfectionistic strivings.